MASCULINITY IN INTERSECTIONALITY: Oppression through Obscurity in the Muslim and Malay Community in Southeast Asia - Latiff, Haikel Fansuri Mohamed (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2022)
This article investigates the appearance of a defined form of masculinity within various aspects of identity in the Muslim and Malay communities in Southeast Asia. This appearance enables for a multilayered understanding of masculinity and hegemonic masculinity which is reinforced by various institutions that fosters and defines the various components of identity. This is by itself a source of tension for men both for the expectations and performance of masculine roles as well as the struggle for a coherent masculinity despite the tensions from the different aspects of identity. Additionally, this article further posits that the very existence of masculinity in these various overlapping aspects presents an opportunity for obscurity by design for the purposes of mystifying masculinity, its functions and ultimately its authority in various institutions and situations. Therefore, the resulting tension and difficulty in defining masculinity on its own terms is the result of this purposeful obscurity where definition, enforcement, policing, and the construction of meaning can only be done through understanding the intersectional location of masculinity. To attempt to dissect this, the article explores masculinity via the following threads, where do we explore the tenets of hegemonic masculinity and the ‘normal’ man? Where are roles and definitions of masculinity obscured by design? And the following debate around the crisis of masculinity.